Soil genesis classification and land use of some soils in the upper Mahanadi Basin - Mishra, Antaryami; Mishra, Ajay Kumar; Dash, Prava Kiran (Springer, Singapore, 2025)
"The Mahanadi River Basin covers approximately 75% of the geographical area of the state of Odisha and spans 23 districts. Its ecological balance depends on the preservation of the soil and forest resources of these districts. The entire area consists of hilly tracks and undulating topography with distinct toposequences. Hence, a detailed study of the soil morphology, genesis and classification of riverside areas is used as the basis for the preservation of its ecosystem. In this present investigation, selected pedons representing different land types in a toposequence in the upper Mahanadi basin were studied in detail, with the land types being hill slope land, upland land, medium land, lowland land and stream terrace land, which represent the ideal topography of the basin. The leaching of basic cations from the A to B horizons in the process of eluviation and illuviation is well evidenced. Out of the 12 orders in soil taxonomy, Alfisols, Inceptisols, Entisols and Vertisols are present here. The hill slopes and uplands are suitable for forest species, timbers and plantation crops such as sisal for soil conservation, cashew, mango, guava, custard apple, litchi, orange, drumstick, plumeria, pineapple, etc. The medium lands are suitable for vegetables, pulses and oilseeds. The lowlands are most suitable for growing rice. "